EFFICIENCY ON GROUP PROPHYLAXIS OF IODINE DEFICIENCY IN CHILDREN LIVING IN IODINE DEFICIENCY REGION - V.R. Kuchma; N.A. Belyakova; A.V. Lareva; M.B. Lyasnikova (Вопросы современной педиатрии)
A complex examination detected that kalium iodide dosage 100 mkg daily promote a rapid normalization of median of ioduria in children aged 8 to 12 years. Even in a case of normal initial level of ioduria iod active at the same dosage doesn't promote an increase of median of ioduria over than optimum level. It wasn't detected any decrease of goiter frequency during 6 months of prophylaxis, while the level of some cognitive indexes (an attention) and the frequency of absence from school by the reason of acute respiratory deseases significantly increased. It could be concluded, that iodine prophylaxis using iod active is more effective in mild goiter endemia combine to decrease of attention in prepubertal children. In the case of combination of moderate endemic goiter and normal cognitive function kalium iodide is more preferable in prophylaxis in children.Key words: children, iod deficiency, prophylaxis.